Latvių kalbos žodžių darybos tyrimų istorija - Navickaitė-Klišauskienė, Agnė (Baltistica, 2009)
THE HISTORY OF WORD FORMATION RESEARCH IN LATVIAN LANGUAGE The purpose of this article is to review the main studies and descriptions of Latvian word formation. The object of the article are the thoughts of authors that have been imparted in Latvian books on grammar, and descriptions, particular articles and other works about Latvian word formation. The endeavour of this article is to compare the conception of word formation in different works, to observe the development of linguistic thought in Latvian word formation as a separate field in Latvian linguistics.